Adopsi Financial Technology, Literasi Keuangan, dan Keberlanjutan Coffee Shop di Kabupaten Badung: Peran Moderasi Dari Perceived Cost - Ni Kadek Dwi Permatasari; Ketut Tanti Kustina (Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the effect of financial technology and financial literacy on the sustainability of coffee shops in Badung Regency, as well as to examine the role of perceived cost as a moderating variable. The background of this research is based on the rapid growth of the coffee shop industry in the Badung tourism area, which requires business actors to enhance digital capabilities and financial management in order to maintain business sustainability. Using the Extended Resource-Based View (E-RBV) approach, this study explains how technology- and knowledge-based resources can strengthen the competitive advantage of coffee shops. The research method employed is quantitative, using Partial Least Squares–Structural Equation Modeling (PLS-SEM) and involving 100 respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire and processed using SmartPLS version 4. The results show that financial technology has a positive and significant effect on coffee shop sustainability, as does financial literacy, which is also proven to have a positive and significant impact. However, perceived cost does not moderate the relationship between financial technology or financial literacy and sustainability, indicating that the benefits of technology and financial knowledge outweigh the perceived cost barriers for business actors. These findings confirm that digital capabilities and accounting skills are crucial elements in strengthening coffee shop sustainability in the digital era.